1971
DOI: 10.1139/v71-532
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Steric Effects on Nitromethylene Acidity and the Mechanism of Epimerization in Partially Blocked Nitro Hexoses

Abstract: The extent of nitronate formation in seven methyl 4,6-O-benzylidene-3-deoxy-3-nitrohexopyranosides and four methyl 4,6-O-benzylidene-2,3-dideoxy-3-nitrohexopyranosides in dilute potassium hydroxide solution was compared by means of u.v. spectroscopy. Considerable differences were found to exist in the nitromethylene acidities, and these were correlated with stereochemical features of the molecules. A facile manno → gluco epimerization occurring in this series was investigated. It was shown that, in alkaline al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In the account that follows, the chemistry of compounds having a cis-fused 4,6-benzylidene acetal ring will be treated first, and that of trans-fused acetals will be dealt with thereafter. A recent study (9) had revealed considerable differences in the ease of nitronate formation (i.e., proton abstraction from C-3) in dependence of the over-all configuration of the molecule. Since the process of nitronate formation has to precede introduction of a halogen atom it could be expected that there would also be a strong influence of configuration upon the course of halogenation.…”
Section: Les Glycosides Analogues Nitro Ayant Les Configurations P-o-mentioning
confidence: 99%
“…In the account that follows, the chemistry of compounds having a cis-fused 4,6-benzylidene acetal ring will be treated first, and that of trans-fused acetals will be dealt with thereafter. A recent study (9) had revealed considerable differences in the ease of nitronate formation (i.e., proton abstraction from C-3) in dependence of the over-all configuration of the molecule. Since the process of nitronate formation has to precede introduction of a halogen atom it could be expected that there would also be a strong influence of configuration upon the course of halogenation.…”
Section: Les Glycosides Analogues Nitro Ayant Les Configurations P-o-mentioning
confidence: 99%
“…Separation was achieved on a silica gel column (100 g) using the same solvent. The fastermoving product (14) was obtained as a solid that was recrystallized from carbon tetrachloride -petroleum ether; m.p. 92-93".…”
Section: -Bromo-13-di-o-met/~yl-2-nitrocyclohexa11e-i 3-diol (14)mentioning
confidence: 99%
“…8 it reacts, even without boron trifluoride catalysis, to give nitronic esters that may subsequently undergo various kinds of irreversible transformations (13a). F o r nitro sugars, pK, values of 8-11 have been reported (11,14), suggesting that some of them might be borderline cases in this respect. The selective methylation of hydroxyl groups in 1 placed confidence in possible applications o f diazomethane t o nitro sugars for which the customary base-promoted alkylation methods, although never actually tried, prima facie do not recommend themselves, both because they would Can.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…It has been realized in those studies that the effect (41, the nonbonded interaction between a group attached by a double bond to the ring (here, =NO,-) and a vicinal, equatorial substituent (here, -OH), has a profound influence upon conformational preferences and configurationai interconversions (2,3). On the basis of free energy calculations (2) one may predict the behavior of other groups of nitro glycosides in alkaline solution, and it is the purpose 'Part XXV in a series on reactions of nitro sugars.…”
Section: Introductionmentioning
confidence: 99%